"Nobody Came to Monte Carlo To Be Bored": The Scripting of the Monte Carlo Pleasurescape 1880-1940. (November 2022) - Franke, Paul
In 1863, the Monegasque government and the newly founded Société des Bains de Mer decided to transform a small hill known as Spélugues into a casino district. Three years later, in 1866, Monte Carlo was officially founded. Over the next three decades, it became a cosmopolitan pleasurescape designed for a nonlocal, seasonal population of gamblers and consumers, separated from the neighboring urban entities. Although not a port city, Monte Carlo constituted a distinctly global space in which the casino company scripted the movements, emotions, and behaviors of visitors for the purpose of gambling and leisure. Monte Carlo represents both a pleasurescape and company town where entertainment and capitalism were prerequisites for its urbanization.